Laparoscopic Port Insertion Modifications According to the Surgeons Competency - Saira Bajwa, Ghazala, Muhammad Ahmad, Bushra Mehmood, Muhammad Faisal (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of current study is to determine the efficacy and safety of laparoscopic port insertion modifications according to the surgeons competency. Study Design: Retrospective study Place and Duration: Sir Ganga Ram Hospital Lahore. Jan-2019-July 2019 Methods: There were 88 patients of both genders were presented in this study. Patients were aged between 17-55 years. Data on the recruited patients’ age, gender, and BMI were compiled after informed written permission was obtained. Indication of surgery was observed first and all of the patients were underwent for laparoscopic surgery port insertion either open or closed . Post-operative efficacy, complication and frequency of mortality was calculated within a duration of 2-months. SPSS 18.0 was used to analyze all data. Results: Among 88 patients, 88 (54.4%) were males and 40 (45.6%) were females. The mean age of the cases were 35.14±11.34 years and had mean BMI 22.6±1.19 kg/m2. Most common indication was inguinal hernia found in 35 (39.8%), appendicitis found in 28 (31.8%) patients, cholelithiasis in 15 (17.05%), varicocele in 6 (6.8%) and benign masses in 4 (4.5%) patients. In 70 (79.5%) patients laparoscopic closed technique was applied and 18 (20.5%) received open technique. Mean time of port insertion was 3.8±5.51 minutes in closed laparoscopy while in open laparoscopy mean time was 2.5±.4.31 minutes. Overall difficult entry was found among 20 (22.7%) cases. Post-operative rate of complications was found among 4 (4.5%) patients in which port site seroma, intraperitoneal injury and infection was the most common. No any mortality found in this study. Patients satisfaction rate was 80 (90.9%). Conclusion: We concluded in this study that laparoscopic port insertion technique was an effective in terms of less operative time, surgeons competency, low rate of mortality and fewer post-operative complications among patients underwent for surgery with different type of diseases.